THE EFFECT OF EXPERIENTIAL LEARNING MODEL BASED ON THE SUKURAGA PUPPETS FOR SOCIAL SKILLS IN ELEMENTARY SCHOOL - Siti Nurzafirah; Dyah Lyesmaya; Iis Nurasiah (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2023)
This paper discusses the effect of the learning model experiental learning based on the Wayang Sukuraga for social skills in elementary schools. The samples are 30 students, which were 15 students in the control class who were not given treatment and 15 students in the experimental class who were given the treatment of experiental learning model. The data used are pre-test and post-test data. The research method used is the experimental method with a quasi-experimental research design with a Non-equivalent control group design. The instruments used are questionnaires and observation sheets. The analysis technique used is hypothesis testing with a simple linear regression test. The hypothesis results indicate that sig was 0.002 and 0.014. The data results are significant < 0.05. Therefore, it can be concluded that there is an effect of the experiential learning model based on the Wayang Sukuraga for social skills in elementary schools.